(untitled) (Pulse, 2025)
Background: Squamous cell carcinoma (SCC) of the oral tongue commonly metastasizes to regional cervical lymph nodes, but distant skeletal metastases are exceedingly rare. Case Presentation: We report a 54-year-old male diagnosed with grade I SCC of the right lateral tongue with regional lymph node metastasis. Following surgical excision and neck dissection, the patient received concurrent chemoradiotherapy. Despite no locoregional recurrence during follow-up, the patient developed isolated bony metastasis to the right ischium ten months post-diagnosis. Histopathology confirmed poorly differentiated SCC at the metastatic site. Palliative radiotherapy and bisphosphonates led to symptomatic improvement. Conclusion: This case highlights the rare occurrence of bony metastasis in primary tongue carcinoma and emphasizes the importance of prolonged, vigilant follow-up and multidisciplinary care to detect and manage atypical disease progression. Pulse Vol.17, 2025 P: 37-40